2008
DOI: 10.1111/j.1439-0531.2008.01145.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive Monitoring of Hormones: A Tool to Improve Reproduction in Captive Breeding of the Eurasian Lynx

Abstract: The survival of many critical endangered mammal species is often depending on successful captive breeding programmes which include the future option of reintroduction to the wild. Breeding in captivity also demands the application of modern assisted reproductive techniques to ensure maximal biodiversity, but knowledge on reproductive physiology is often limited. Therefore, non-invasive monitoring of urinary and faecal hormones has become an important tool for reproductive management. To exemplify the importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 39 publications
(38 reference statements)
4
28
0
Order By: Relevance
“…Interestingly, the highest oestrogen concentrations were found in CLs of pregnant lynxes, signalling an involvement of this steroid in the maintenance of pregnancy. Non-invasive monitoring of steroids in urine and faecal samples of Eurasian and Iberian lynxes corroborates the special role of oestrogens during pregnancy in lynxes; showing elevated profiles of urinary and faecal oestrogen metabolites in pregnant animals, which were correlated to progestin metabolites (Dehnhard et al 2008). In contrast to P 4 , elevated oestrogens were not reflected in serum oestradiol (E 2 ) levels (Gö ritz et al 2009).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Interestingly, the highest oestrogen concentrations were found in CLs of pregnant lynxes, signalling an involvement of this steroid in the maintenance of pregnancy. Non-invasive monitoring of steroids in urine and faecal samples of Eurasian and Iberian lynxes corroborates the special role of oestrogens during pregnancy in lynxes; showing elevated profiles of urinary and faecal oestrogen metabolites in pregnant animals, which were correlated to progestin metabolites (Dehnhard et al 2008). In contrast to P 4 , elevated oestrogens were not reflected in serum oestradiol (E 2 ) levels (Gö ritz et al 2009).…”
Section: Discussionsupporting
confidence: 55%
“…Duplicates of the extracts (20 and 10 ml respectively) were tested for both P 4 and oestrogens using in-house 96 well microtitre plate enzyme immunoassays previously validated for the Eurasian lynx (Dehnhard et al 2008). P 4 analyses were carried out as described earlier ) using a commercial P 4 antibody (Sigma P1922, raised in rats) and 4-pregnen-3,20-dione-3-CMO-peroxidase label.…”
Section: Intraluteal Steroid Hormone Determinationmentioning
confidence: 99%
“…A previous study in domestic cats described that progesterone was excreted primarily as conjugated metabolites and unconjugated pregnanolone epimers (primarily 5β-pregnan-3α/β-ol-one) and that progesterone is not detected [15]. Fecal progesterone metabolites in the female Eurasian lynx also contained 5α-pregnan-3β-ol-20-one and 5α-pregnan-3,20-dione [8]. Progesterone has not been usually detected in the feces of wild felid species, such as the tiger (Panthera tigris), lion (P. leo) [16], leopard cat (Felis bengalensis), clouded leopard (Neofelis nebulosa) and snow leopard (Uncia uncia) [15].…”
Section: Discussionmentioning
confidence: 87%
“…However, information about the types of fecal hormone metabolites among the reproductive stages is limited. It has been reported that in the Eurasian lynx (Lynx lynx), the excretion pattern of fecal progestagen metabolites is different among pregnancy stages [8]. Understanding the excretion pattern, such as the components of fecal hormone metabolites, among reproductive stages is important for validating the assay method used for monitoring the stages.…”
mentioning
confidence: 99%
“…In contrast to other felids, steroid-based monitoring of ovarian luteal function is impossible using fecal and urinary progestagen metabolites, therefore a reliable pregnancy diagnosis method has never before been developed [8,25]. The Witness relaxin pregnancy test [13] has been used for diagnostic purposes using urine samples collected between Days 26 and 46 from pregnant Iberian lynx [10].…”
Section: Discussionmentioning
confidence: 99%